Ambidextrous AI Governance for Driving SmartCo’s Digital Transformation Using COBIT 2019 Traditional and DevOps - Azzahra, Octamevia Inkaputri; Mulyana, Rahmat; Adi, Taufik Nur (International Journal of Advances in Data and Information Systems, 2025)
Artificial Intelligence (AI) plays a vital role in accelerating digital transformation within the technology sector. This study investigates SmartCo, a technology company seeking to enhance the security and governance of AI implementation using an ambidextrous COBIT 2019 framework that integrates people, processes, and technology. The research adopts a Design Science Research (DSR) methodology, utilizing interviews, questionnaires, and internal document analysis until data saturation was achieved. Governance and Management Objectives (GMOs) were prioritized using design factors, DevOps practices, relevant regulations (ICT Minister Regulation No. 5/2021 and SOE Minister Regulation No. PER-2/MBU/03/2023), and previous studies. DSS05 (Managed Security Services) was selected as the primary focus, reflecting the organization’s priority on data protection and secure AI operations. The capability maturity assessment revealed gaps in security leadership, documentation, and process automation, indicating the need for more adaptive and integrated governance. Targeted improvements were implemented, including formalizing governance structures, enhancing security training, and adopting supportive technologies, which increased the DSS05 maturity level from 3.00 to 3.86. A comprehensive roadmap guides further enhancements in security-focused governance. This study provides practical insights for organizations aiming for secure, AI-enabled digital transformation. In addition, it contributes to the theoretical foundation of ambidextrous COBIT 2019 governance frameworks by demonstrating their application in a regulated technology environment.